Solving linear differentiation equation system using fuzzy logic - Esraa M.B.Alobady; Neam H. Alfahady (Genius Journals, 2023)
In recent years, various interests in fuzzy set theory have emerged as a generalization of ideas from classical set theory. In this research, the classical mathematical equations of various types and their development were studied from the perspective of fuzzy logic, and the representation of the system of linear fuzzy equations was discussed and some methods of solving them were presented. We have adopted a combative approach between the classical method and the fuzzy logic method in the scientific presentation of the material in this thesis in order to highlight the advantages of the general theory of the fuzzy group theory. It also promotes the theoretical aspects arising from many detailed examples. The demonstration shows that the results of fuzzy logic are consistent with the classical results, and that the fuzzy results are flexible and generalizable.
Keywords: flexible; various; results; generalizable